2010
DOI: 10.1038/npp.2010.28
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Effects of Increased and Decreased Dopamine Transmission on Latent Inhibition in Ovariectomized Rats and Their Modulation by 17β-Estradiol: An Animal Model of Menopausal Psychosis?

Abstract: Women with schizophrenia have later onset and better response to antipsychotic drugs (APDs) than men during reproductive years, but the menopausal period is associated with increased symptom severity and reduced treatment response. Estrogen replacement therapy has been suggested as beneficial but clinical data are inconsistent. Latent inhibition (LI), the capacity to ignore irrelevant stimuli, is a measure of selective attention that is disrupted in acute schizophrenia patients and in rats and humans treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 137 publications
3
13
0
Order By: Relevance
“…17b-estradiol at 50 and 150 mg/kg doses, which potentiated LI under conditions that disrupted LI in untreated gonadally intact rats (strong conditioning), also reversed amphetamine-induced LI disruption, as typically found with APDs. The present results replicate our recent finding (Arad and Weiner, 2010) that 17b-estradiol prevents amphetamine from disrupting LI in gonadally intact female rats and extends this action of 17b-estradiol to gonadally intact male rats. Sex-dependent antipsychotic capacity of 17b-estradiol M Arad and I Weiner…”
Section: Reversal Of Disrupted Li: Putative Efficacy For Positive Symsupporting
confidence: 95%
See 4 more Smart Citations
“…17b-estradiol at 50 and 150 mg/kg doses, which potentiated LI under conditions that disrupted LI in untreated gonadally intact rats (strong conditioning), also reversed amphetamine-induced LI disruption, as typically found with APDs. The present results replicate our recent finding (Arad and Weiner, 2010) that 17b-estradiol prevents amphetamine from disrupting LI in gonadally intact female rats and extends this action of 17b-estradiol to gonadally intact male rats. Sex-dependent antipsychotic capacity of 17b-estradiol M Arad and I Weiner…”
Section: Reversal Of Disrupted Li: Putative Efficacy For Positive Symsupporting
confidence: 95%
“…We have previously obtained this same bimodal effect of 17b-estradiol on LI in OVX rats (Arad and Weiner, 2010) and Nofrey et al (2008) have also reported LI-disrupting effect of 10 mg/kg 17b-estradiol in OVX rats. The fact that 17b-estradiol produces contrasting effects on LI at low and high doses implies that estradiol acts dose-dependently on different neural substrates.…”
Section: Bimodal Effect Of 17b-estradiol On LIsupporting
confidence: 59%
See 3 more Smart Citations